2014
DOI: 10.3390/pharmaceutics6030366
|View full text |Cite
|
Sign up to set email alerts
|

Release of Tenofovir from Carrageenan-Based Vaginal Suppositories

Abstract: Microbicides are an active area of research for HIV prevention, being developed as a woman-initiated method of prevention during unprotected coitus. Along with safety and efficacy, assessing and improving compliance is a major area of research in microbicide development. We have produced microbicide prototypes in the form of semisoft vaginal suppositories prepared from carrageenan and conducted both qualitative and quantitative studies using these prototypes to determine the physical properties that drive acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…For diffusion into 5 mL VSF, 45-50 % of TFV was released in the first 2 h, 60 % within 6 h and 70 % in 24 h (Figure 7). Previous studies with 5 mL of dissolution medium indicated that release plateaus at 24 h [21]. Recognizing the limitation of insufficient sink conditions, for the 5 mL drug diffusion studies, the dissolution medium was replenished with fresh VSF at 24 h to stimulate additional release.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For diffusion into 5 mL VSF, 45-50 % of TFV was released in the first 2 h, 60 % within 6 h and 70 % in 24 h (Figure 7). Previous studies with 5 mL of dissolution medium indicated that release plateaus at 24 h [21]. Recognizing the limitation of insufficient sink conditions, for the 5 mL drug diffusion studies, the dissolution medium was replenished with fresh VSF at 24 h to stimulate additional release.…”
Section: Resultsmentioning
confidence: 99%
“…The carrageenan-based semisoft suppositories are being developed to release the active pharmaceutical ingredient (API) and slowly disintegrate within the body so that any resultant discharge mimics vaginal mucous secretions. Our initial prototypes formulated with carrageenan alone successfully released drug [21], but did not disintegrate when exposed to a simulated vaginal environment (i.e., a small volume (5 mL) of vaginal simulant fluid at 37 °C). Accordingly, we are investigating addition of other polymers, such as carbopol, to carrageenan formulations to aid with breakdown in a simulated vaginal environment.…”
Section: Introductionmentioning
confidence: 99%
“…Vaginal suppositories have been previously used to deliver probiotics for general vaginal health. Microbicides formulated into vaginal suppositories have also been reported [96]. Zaveri et al has shown incorporation of TFV into semisoft vaginal suppositories prepared using a carrageenan base, which offered evidence of anti-HIV activity [96].…”
Section: On-demand Vaginal Rectal and Dual Compartment Dosage Formsmentioning
confidence: 99%
“…Microbicides formulated into vaginal suppositories have also been reported [96]. Zaveri et al has shown incorporation of TFV into semisoft vaginal suppositories prepared using a carrageenan base, which offered evidence of anti-HIV activity [96]. Similar to gels, suppositories can be prepared as dual compartment products.…”
Section: On-demand Vaginal Rectal and Dual Compartment Dosage Formsmentioning
confidence: 99%
“…But, the main problems with vaginal films and vaginal gels are their low drug content, wetting and leakage. [20][21][22] Similarly, vaginal tablets cause irritation, hypertonic and discomfort as it takes more time for disintegration. Hence, there is a need to explore an intermediate product for the treatment of this infection which exist between gels/ films and tablets.…”
Section: Introductionmentioning
confidence: 99%